World music [ a global journey - Miller, Terry E.; Shahriari, Andrew (Routledge, 2009)
Introduces students to the diversity of musical expression around the world. This title takes the reader across the globe to experience cultural traditions that challenge the ear, the mind, and the spirit. It presents a systematic study of varied traditions in a non-technical language accessible to various enthusiasts of world music and culture